Alternative bone expansion technique for immediate placement of implants in the edentulous posterior mandibular ridge: a clinical report - (:unkn) unknown (My University, 2004)
PURPOSE: The aim of this study was to evaluate the effectiveness of a split-crest bone augmentation technique performed for immediate implant placement in thin edentulous posterior mandibular ridges. MATERIALS AND METHODS: In the present study, 125 implants were placed in posterior mandibular ridges of 30 patients. The mandibular buccal walls were split, expanded, and grafted with a combination of platelet-rich plasma and Cerasorb. The split segments were held in place by cortical bone screws. Before loading, periodontal status was checked, implant stability was evaluated with the Periotest, and panoramic radiographs and computerized tomography scans were obtained. Second-stage surgery (cover screw removal and healing abutment placement) was performed after 3 to 4 months. RESULTS: All implants osseointegrated successfully and underwent loading after 4 months. Optimal healing occurred 3 to 4 months earlier than the usual 6 to 9 months required, and no lip paresthesia was noted. DISCUSSION: Although onlay-inlay grafts, sandwich osteotomies, guided bone regeneration, piezoelectricity, and alveolar distraction have been indicated for augmentation in the posterior mandibular region, each of these techniques involves risks and complications. The crest-splitting bone expansion technique enables single-stage immediate implant placement and lateral ridge augmentation in thin crests and may prevent neurosensorial deficiencies. CONCLUSIONS: The split-crest surgical technique is a valid reconstructive procedure for sharp posterior mandibular ridges. If performed using platelet-rich plasma and Cerasorb, it can shorten the osseointegration period.
Keywords: Female; Humans; Middle Aged; Male; Time Factors; Mandible; Dental Implantation, Endosseous; Dental Prosthesis Retention; Blood Platelets; Alveolar Ridge Augmentation; Bone Substitutes; Bone Screws; Osseointegration; Calcium Phosphates; Dental Implants; Plateletpheresis